“I GOT STUCK NOT ONLY IN THE FIRST ESSAY”: A NARRATIVE INQUIRY ON STUDENTS’ WRITING DIFFICULTIES - Rachel Gisela Purba; Susana Teopilus (Widya Mandala Surabaya Catholic University, 2023)
Writing, one of the language skills, seems to be the most difficult skill for students to master. There are five aspects used to evaluate students’ writing abilities: content, organization, vocabulary, language use, and mechanics. This current narrative inquiry research aims to find out students’ difficulties in writing expository essays, the factors that cause them to have difficulties, and the strategies they use to overcome them. The data of this research were taken from the students taking Writing Expository and Argumentative Essays course in the English Department of Widya Mandala Surabaya Catholic University. The data of this study were collected from interviews, observations, and documents. Three participants with middle-achievement levels were interviewed in three interview sessions, and observations in the writing class were conducted two times. Besides, two essays of each participant were analyzed.The findings show that in relation to the five writing aspects, the major difficulty that the participants had was in the content aspect. Then, the common factor that caused all of the participants to have difficulties was a lack of reading habit. Besides, the common strategy that all participants used to overcome their difficulties was to search on Google.